Identifikasi Taman Ramah Anak di Kota Semarang - Fika Franestia; Roro Purbaningrum Suratno; Novia Sari Ristianti; Mussadun Mussadun; Rina Kurniati (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2022)
Provision of parks in urban areas must consider the needs of children. The existence of a child-friendly park has a goal to fulfill children's rights. Child-friendly parks are closely related to Child Friendly City which is one of the things that the City of Semarang wants to achieve. Children's activities in the playground will be more meaningful if safe and comfortable facilities are available so that children do not feel bored. The purpose of this study was to assess the condition of the park in the city of Semarang as a child-friendly park. Based on this assessment, an evaluation of the provision of child-friendly parks in the city of Semarang was compiled. The method used is scoring. After knowing the score for each park, the percentage of the park as a child-friendly park is calculated. The results showed that Taman Bumi Rejo, Kedondong, and Citra Satwa were suitable as child-friendly parks. Meanwhile, Tirto Agung Park cannot be said to be a child-friendly park because there are several indicators that have not been met. The evaluation given is that special care and supervision is needed so that the condition of the park is suitable as a place for children to play. Some facilities need updating such as play furniture, soft mats, and toilets. This research can be useful for the Semarang City government in improving the condition of the park so that it is safer for children.